2019
DOI: 10.3389/fphar.2019.00965
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events in Patients With Rheumatoid Arthritis and Psoriatic Arthritis Receiving Long-Term Biological Agents in a Real-Life Setting

Abstract: Background: Biological agents used for the treatment of psoriatic arthritis (PsA) and rheumatoid arthritis (RA) are associated with serious adverse effects (SAEs). Although several biologics have demonstrated good efficacy and tolerability in short-term trials, treatment guidelines recommend them as third line therapies due to a relative lack of long-term safety data. Objective: To determine the frequency and severity of adverse effects associated with the long-term use of biologics in the treatment of PsA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 59 publications
7
23
0
Order By: Relevance
“…In the present study, the main biotech drugs related to ADRs were adalimumab and etanercept, in agreement with other studies [13,15,22], but the incidence per 100 patients per year was higher than that reported in Spain in patients with rheumatoid arthritis (8.1 for adalimumab and 5.1 for etanercept) [19]. The incidence in our study was determined in a general manner for all ADRs, while the Spanish study only considered serious ADRs [19].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the present study, the main biotech drugs related to ADRs were adalimumab and etanercept, in agreement with other studies [13,15,22], but the incidence per 100 patients per year was higher than that reported in Spain in patients with rheumatoid arthritis (8.1 for adalimumab and 5.1 for etanercept) [19]. The incidence in our study was determined in a general manner for all ADRs, while the Spanish study only considered serious ADRs [19].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, according to severity, 22.6% of the reports were classified as serious, consistent with what was found in Italy (9.8-25.5%) [15,23], Japan (18.5-23.4%) [20,26], Spain (21.7%) [19], Brazil (25.0%) [22] and Korea (32.3%) [12]. Among severe reactions, the possibility of developing cancer, infections, hypersensitivity reactions and major cardiovascular events is described in the literature [10,12,14,19,22], and fatalities can also occur, which in this report corresponded to 0.1% of all ADRs, a rate lower than that documented in another study [27]. Death does not correspond to an adverse event but rather to a fatal outcome that can also be explained by the underlying disease of the patient.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…New technologies are registered based on controlled and randomized clinical trials, in which, in most cases, they fail to capture important safety results that only appear in real-life studies ( Lopes et al., 2014 ; Fulone et al., 2018 ; De Carmago et al., 2019 ). In addition, in the case of new cancer medicines, often licensed on the basis of limited information, which can cause concern and wasted resources ( Pontes et al., 2020 ).…”
mentioning
confidence: 99%